2012
DOI: 10.1097/ta.0b013e31825a7723
|View full text |Cite
|
Sign up to set email alerts
|

The impact of injury severity and transfer status on reimbursement for care of femur fractures

Abstract: Prognostic/epidemiologic study, level III. Economic analysis, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
2
15
1
Order By: Relevance
“…Higher severity is associated with less underreporting, and there are fewer barriers to determining causality for trauma compared with chronic injuries or illnesses [Morse et al, 2000;Shannon and Lowe, 2002]. A recent study at a Level I trauma center also found that higher severity patients were more likely to have an identified payer [Nahm et al, 2012]. However, we did observe a differential with respect to payer.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Higher severity is associated with less underreporting, and there are fewer barriers to determining causality for trauma compared with chronic injuries or illnesses [Morse et al, 2000;Shannon and Lowe, 2002]. A recent study at a Level I trauma center also found that higher severity patients were more likely to have an identified payer [Nahm et al, 2012]. However, we did observe a differential with respect to payer.…”
Section: Discussioncontrasting
confidence: 68%
“…The mechanism is unknown, but could be related to hospitals being more highly motivated to identify all potential payers for more severe (and presumably more costly) injuries. A recent study at a Level I trauma center also found that higher severity patients were more likely to have an identified payer [Nahm et al, 2012]. In Washington State, the covered population does not include federal employees or exempt/excluded employment [State of Washington, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…This comports with previous findings from Washington State (Sears et al. ) and Ohio (Nahm, Patterson, and Vallier ). This pattern could be related to hospitals being more highly motivated to identify all potential payers for more severe (and presumably more costly) injuries.…”
Section: Discussionsupporting
confidence: 92%
“…While in some cases accepting transfer patients results in a greater proportion of patients without insurance or with Medicaid,[9, 10] in other cases inter-hospital transfer does not alter or even improves a facility's payer mix. [11, 21, 22]…”
Section: Discussionmentioning
confidence: 99%